Pemanfaatan Limbah Kopi Arabika menjadi Selai Cascara di Desa Mendale Aceh - Kamarudin, Anna Permatasari; Budi, Hasiun; Efendi, Muhsin; Yuniara, Ridha; Ramadhan, Masri; Fadli, Fadli (Universitas Pahlawan Tuanku Tambusai, 2025)
Arabica cofee is a major export commodity and a mainstay in Central Aceh. However, it leaves a lot of waste in areasr adjacent to coffee processing businesses. The increasing accumulation of cofee husk waste pollutes the soil, air, and water. One way to utilize this waste is by processing it onto jam. Jam processing is carried out by taking fresh red coffee husks from pulping. The purpose of this Community Service Program is to provide knowledge about the benefits and efficacy of coffee husk (cascara) and to process the husk into cascara jam. A total of 20 partners attended this program, consisting of village women and women from the Family Welfare Movement (PKK). The methods used were presentation by resource percons through lectures, demonstrations, and training. The results of this activity showed that partners were previously unaware that cascara husks are edible and have an acceptable organoleptic taste. Partners’ knowledge has increased after participating in this activity.